2022
DOI: 10.3390/microorganisms10071314
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in a COVID-19 Non-ICU Department: Microbial Epidemiology, Resistance Profiles and Comparative Analysis of Risk Factors and Patients’ Outcome

Abstract: Background: Bloodstream infections (BSI) caused by highly resistant pathogens in non-ICU COVID-19 departments pose important challenges. Methods: We performed a comparative analysis of incidence and microbial epidemiology of BSI in COVID-19 vs. non-COVID-19, non-ICU departments between 1 September 2020-31 October 2021. Risk factors for BSI and its impact on outcome were evaluated by a case-control study which included COVID-19 patients with/without BSI. Results: Forty out of 1985 COVID-19 patients developed BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
2
15
0
3
Order By: Relevance
“…In line with our results, a recently published study also reported that all of their A. baumannii isolates collected from COVID-19 patients were CR [ 7 ]. Additionally, Sathyakamala et al reported Acinetobacter species as a bacterial pathogen with maximum antimicrobial resistance among COVID-19 and non-COVID-19 patients admitted to the ICU [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with our results, a recently published study also reported that all of their A. baumannii isolates collected from COVID-19 patients were CR [ 7 ]. Additionally, Sathyakamala et al reported Acinetobacter species as a bacterial pathogen with maximum antimicrobial resistance among COVID-19 and non-COVID-19 patients admitted to the ICU [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, MDR A. baumannii infections were reported as one of the most prevalent bacterial co-infection in patients with COVID-19 [ 7 , 8 ]. The use of corticosteroids and anti-IL6-directed therapies in COVID-19-positive patients suppresses the immune system and causes a high incidence of microbial co-infections in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the hospital A reported the most infected and dead patients. Therefore, CR- A. baumannii outbreaks in this hospital could be partly associated with shortages in personnel, personal protective equipment, and dedicated medical equipment, which had affected the conventional infection prevention and control practices [ 7 ]. To this end, the hands of healthcare workers can act as vehicles for transmission either from a colonized patient to other patients or contaminated surfaces to patients.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA je proteklih godina bila suprimirana ponovo se pojavila kao česti uzročnik bolničkih infekcija, a porastao je broj infekcija uzro kovanih Acinetobacter sp. i MR K. pneumoniae 9 . Odr žavanje higijene ruku postalo je glavni problem unu tar pretrpanih bolničkih kapaciteta i mjera osobne zaštite 10 .…”
Section: Raspravaunclassified